Quercetin in Shengxian Decoction exhibits anti-ferroptosis protective roles in a myocardial infarction model via targeting DPP4/ HMOX1, based on network pharmacology and molecular docking - Zhai, Yuming; Fu, Jiamei; Yang, Jianfei; Zhou, Yabin (Frontiers in Pharmacology, 2025)
BackgroundMyocardial infarction (MI) is characterized by high morbidity. In this study, we aimed to elucidate potential targets of Shengxian Decoction (SXD) against MI.MethodsPairing of SXD active ingredients and MI targets was conducted using the Chinese Medicine System Pharmacological Database, Gene Expression Omnibus (GEO), and STRING databases. The effects of SXD on MI were validated in vitro. Molecular docking was verified using cellular thermal shift assay (CETSA).ResultsA total of 40 active ingredients and 28 MI-related targets were obtained. Cross-analysis on 28 targets and cell death-related genes identified two crucial ferroptosis-related targets, namely, dipeptidyl peptidase 4 (DPP4) and heme oxygenase 1 (HMOX1). In cobalt chloride (CoCl2)-induced hypoxic H9c2 cells, SXD could remarkably improve cell viability and inhibit cell death. Meanwhile, SXD treatment significantly affected the ferroptosis-related markers in hypoxic H9c2 cells. Molecular docking and CETSA results showed that quercetin had good binding activity with DPP4 and HMOX1.ConclusionImportant active ingredient quercetin in SXD could exert anti-ferroptosis protective roles on MI through targeting ferroptosis-related genes (DPP4/HMOX1), thereby contributing to the protective role of SXD on MI.